Nanocomposites of ternary mixed metal oxides (Ag2O/NiO/ZnO) used for the efficient removal of organic pollutants. (October 2022) - Bhatia, Pooja; Nath, Mala
Abstract: A facile synthesis of nanocomposites of ternary metal oxides (Ag2 O/NiO/ZnO) has been reported. Three ternary nanocomposites A/N/Z-1, A/N/Z-2, and A/N/Z-3 with different molar ratios of silver oxide (10 %, 20 % and 30 %, respectively) have been synthesized by decorating a binary N/Z (NiO/ZnO = 1:1) nanocomposite. The diameter of the particles in N/Z binary nanocomposite is approximately 31.59 ± 5.03 nm, and the size of the decorated silver oxide in the A/N/Z-3 ternary nanocomposite is 5.92 ± 1.36 nm as deduced from TEM analysis. The Ag2 O/NiO/ZnO nanocomposites have efficiently catalyzed the reduction of various nitrophenols, dyes, and their mixtures. Among the synthesized nanocomposites, A/N/Z-3 has the highest silver oxide content that reduces 4-nitrophenol ([ p NP] = 0.16 mM) in the shortest time (7 min). Therefore, A/N/Z-3 has been chosen to investigate other parameters for p NP's reduction, including the amounts of catalyst, p NP and sodium borohydride. A/N/Z-3 (6.41 μg mL −1 ) reduces different nitrophenols ([NP] = 0.16 mM) in following order: o NP (2-nitrophenol: 2 min) > m NP (3-nitrophenol: 2 min) > p NP (4-nitrophenol: 7 min) > 2, 4, 6TNP (2, 4, 6-trinitrophenol: 13 min) in the presence of sodium borohydride (40 mM). Similarly, A/N/Z-3 (6.02 μg mL −1, except for MB, the amount used was 29.41 μg mL −1 ) reduces different dyes (0.02 mM) in the following order: MO (methyl orange: 2 min and 30 s) > CR (congo red: 2 min and 30 s) > RB (rhodamine-B: 4 min) > MB (methylene blue: 9 min). Further, A/N/Z-3 reduces nitrophenols' mixture, dyes' mixture, simulated effluents (EFF1) sample and a real industrial sample (dye bath effluents: DBE) in 8 min, 8 min, 6 min and 12 min, respectively, and also reused up to five cycles. Hence, this highly efficient, inexpensive, and easily reusable robust catalyst can be used to remove toxic organic pollutants from industrial wastewater. Graphical abstract: Unlabelled Image Highlights: NiO/ZnO (1:1) deposited with 10, 20 and 30 % Ag2 O to synthesize Ag2 O/NiO/ZnO nanocomposites. A/N/Z-3 (30 % Ag2 O) rapidly reduces various nitrophenols, dyes and their mixtures. A/N/Z-3 also tested on simulated and real pollutants sample for their rapid reduction. Good reusability of A/N/Z-3 catalyst was established up to five cycles.